EXPLORING KENAN’S DILEMMAS TOWARD NATIONALISM IN AS LONG AS THE LEMON TREES GROW - Qudsi, Nuha Fauhana (Serat: Journal of Literary & Cultural Studies, 2025)
Nationalism, particularly during war, reaches its upheaval through the lives of civilians who are threatened and yet remain loyal to their country.  Incorporating qualitative methods and critical analysis, this research examines the book As Long as the Lemon Trees Grow by Zoulfa Katouh to explore Kenan's character and the dilemmas he faced in leaving his country during the Syrian Civil War. The objective of this study is to interpret how Kenan's drive for survival, his responsibilities as a husband and eldest brother, and his growing awareness of the atrocities of war can contribute to his nationalism. The research scrutinizes his character as a loyal Syrian civilian faced with the difficult choice of surviving or fleeing the war and becoming a refugee while maintaining his love for Syria. The findings reveal that Kenan's sense of nationalism may influence his final stance to overcome his desire to stay. In Kenan's case, staying meant sacrificing more of his loved ones, so he embraced the chance to flee yet remain bound as a proud Syrian citizen wherever he was. This study argues that nationalism is not limited to the country's location. Kenan's character builds a family-priority perspective, while nationalism becomes part of his enduring identity.